Source
%@Dif:3
\begin{center}
\Eqalign{ &&&\mbox{Forme développée}&&\mbox{Forme factorisée}\cr A&=(3x-5)^2-(3x-5)(x+2)\kern2cm&A&=6x^2-31x+35\kern2cm&A&=(2x-7)(3x-5)\cr B&=(4x-1)(x+5)-(4x-1)^2&B&=-12x^2+27x-6&B&=(4x-1)(-3x+6)\cr C&=(2x-3)^2-(1-4x)(2x-3)&C&=12x^2-26x+12&C&=(2x-3)(6x-4)\cr D&=(a+5)^2-(a-5)^2&D&=20a&D&=20a\cr E&=(3x-4)^2-(3x-4)(3x-3)&E&=4-3x&E&=4-3x\cr F&=(3x+1)(5x-4)-(5x-4)^2&F&=-10x^2+33x-20&F&=(5x-4)(-2x+5)\cr G&=(x+7)^2+3(x+7)&G&=x^2+17x+70&G&=(x+7)(x+10)\cr H&=(3x-2)^2+6(3x-2)&H&=9x^2+6x-8&H&=(3x-2)(3x+4)\cr I&=(2x+3)^2-16&I&=4x^2+12x-7&I&=(2x-1)(2x+7)\cr J&=(4x-5)^2-(2x+1)^2&J&=12x^2-44x+24&J&=(2x-6)(6x-4)\cr K&=(1-2x)^2-(1-2x)(1+2x)&K&=8x^2-4x&K&=4x(2x-1)\cr L&=(3x-1)^2-81&L&=9x^2-6x-80&L&=(3x-10)(3x+8)\cr M&=49-(3x-5)^2&M&=-9x^2+30x+24&M&=(-3x+12)(3x+2)\cr N&=(3x-2)^2-4(3x-2)&N&=9x^2-24x+12&N&=(3x-2)(3x-6)\cr O&=(x+1)^2+(x+1)&O&=x^2+3x+2&O&=(x+1)(x+2)\cr P&=(2x+1)^2-(2x+1)&P&=4x^2+2x&P&=2x(2x+1)\cr Q&=(3x+1)(2x-3)+(3x+1)^2&Q&=15x^2-x-2&Q&=(3x+1)(5x-2)\cr R&=(4x+5)^2-7(4x+5)&R&=16x^2+12x-10&R&=(4x+5)(4x-2)\cr S&=(2x-1)^2-(3x+4)^2&S&=-5x^2-28x-15&S&=(-x-5)(5x+3)\cr T&=(2x+5)(3x-1)+(3x-1)^2&T&=15x^2+7x-4&T&=(3x-1)(5x+4)\cr U&=(5x+1)(2x+4)-(1+5x)^2&U&=-15x^2+12x+3&U&=(5x+1)(-3x+3)\cr V&=(x+1)^2-(x+1)(2x+3)&V&=-x^2-3x+2&V&=(x+1)(-x-2)\cr W&=(7x-2)^2-(8x+3)^2&W&=-15x^2-76x-5&W&=(-x-5)(15x+1)\cr X&=(2x-5)^2+(2x-5)(3x-5)&X&=10x^2-45x+50&X&=(2x-5)(5x-10)\cr Y&=4x^2-4x+1-(3x+2)^2&Y&=-5x^2-16x-3&Y&=(-x-3)(5x+1)\cr Z&=(4x+5)^2-4x^2-12x-9&Z&=12x^2+28x+16&Z&=(2x+2)(6x+8)\cr }
%@Commentaire: Travail en autonomie.